Relationship between oral bacteria count and pneumonia onset in elderly nursing home residents. Issue 4 (11th August 2014) - Kikutani, Takeshi; Tamura, Fumiyo; Tashiro, Haruki; Yoshida, Mitsuyoshi; Konishi, Kiyoshi; Hamada, Ryo
<x xml:space="preserve">Abstract</x> Aim Oral bacteria, which are a source of infection for aspiration pneumonia, were examined in frail older adults with the aim of establishing a standard bacteria count that indicates the risk of pneumonia onset in this group. Methods A survey of bacteria count in the saliva using a simple instrument for measurement of the number of oral bacteria, along with factors including swallowing function and nutritional status, was carried out in 691 elderly individuals requiring care (137 men; mean age 82.6 ± 8.3 years; 554 women; mean age 88.0 ± 7.1 years; total mean age 86.7 ± 7.8 years) at 16 nursing homes in Japan. All participants gave their consent for inclusion in the present study. During a 6‐month follow‐up period, participants who developed pneumonia were identified, and relationships between the factors measured at the start of the period and pneumonia onset were examined. Results During the 6‐month follow‐up period, 33 participants (4.8%; 5 men, 28 women; mean age 88.3 ± 7.4 years) developed pneumonia. Pneumonia onset was significantly associated with reduced activities of daily living, swallowing dysfunction and undernourishment. Logistic regression analysis identified a saliva bacteria count of 108.5 colony‐forming units/mL as an independent explanatory factor for pneumonia onset (P = 0.012, RR = 3.759). Conclusions Oral bacteria count of 108.5 colony‐forming units/mL saliva in an elderly person requiring care was identified as a risk factor for pneumonia onset. Geriatr Gerontol Int 2015; 15: 417–421.